Lupus cystitis with hydroureteronephrosis in a young female with lupus nephritis - Ete, Tony; Mondal, Sumantro; Sinha, Debanjali; Sarkar, Soumik; Bhunia, Abhirup; Kamei, Shingamlung; Pal, Jyotirmoy; Ghosh, Alakendu (International Journal of Research in Medical Sciences, 2017)
Systemic lupus erythematosus is an autoimmune, multisystem disorder. Lupus nephritis is a common manifestation of SLE. Though rare, SLE may also involve lower urinary tract in the form of lupus cystitis with associated complications like hydroureteronephrosis. Lupus cystitis may present with gastro intestinal (GI) symptoms as the initial manifestation. The case reported herein is concerned with concomitant lupus nephritis and cystitis in a young female who also had associated GI symptoms and hydroureteronephrosis.